Factors affecting the pharmaceutical waste management practices of independent community pharmacists in Manila City - Fernandez, Leila Avior R.; Gaspar, Reinier B; Mercado, Jemina Mar C
Pharmaceutical waste management (PWM) in community pharmacies is a growing concern, as improper disposal of medicines can harm both public health and the environment. In the Philippines, independent community pharmacies often lack clear, pharmacy-specific guidelines on waste management, and research on their practices and influencing factors remains limited. This study aimed to determine the factors influencing PWM practices among independent community pharmacists in Manila City.